1999
DOI: 10.1002/(sici)1521-3765(19990802)5:8<2237::aid-chem2237>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Direct Hydride Delivery from Formic Acid in Transfer Hydrogenation

Abstract: The regioselectivity of hydrometalation in transfer hydrogenation was investigated by tracing the fate of the deuterium label in both the formyl and carboxyl positions of formic acid during the isomerization of a cis enol ether. The deuterium from the formyl position is incorporated exclusively into the electron-deficient center of the double bond; this indicates that hydride attack occurs during transfer hydrogenation. The fact that the formyl hydrogen is more reactive than the carboxyl hydrogen suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Given the fact that palladium is well-known to react with acetic during the isomerization of a cis enol ether (Figure 4c). 8 The results showed that the deuterium from the formyl position was incorporated exclusively into the electron-deficient center of the double bond, while the identities of the two hydrogens were not scrambled during the transfer hydrogenation, indicating the formyl hydrogen is more reactive than the carboxyl hydrogen. It was proposed that the isomerization reaction proceed via an intermolecular hydride transfer mechanism with a sixmembered-ring intermediate, similar to the Meerwein− Ponndorf−Verley (MPV) mechanism (Figure 4d).…”
Section: Reaction Mechanisms Of Cth With Famentioning
confidence: 99%
See 2 more Smart Citations
“…Given the fact that palladium is well-known to react with acetic during the isomerization of a cis enol ether (Figure 4c). 8 The results showed that the deuterium from the formyl position was incorporated exclusively into the electron-deficient center of the double bond, while the identities of the two hydrogens were not scrambled during the transfer hydrogenation, indicating the formyl hydrogen is more reactive than the carboxyl hydrogen. It was proposed that the isomerization reaction proceed via an intermolecular hydride transfer mechanism with a sixmembered-ring intermediate, similar to the Meerwein− Ponndorf−Verley (MPV) mechanism (Figure 4d).…”
Section: Reaction Mechanisms Of Cth With Famentioning
confidence: 99%
“…In transfer hydrogenation, FA that contains active hydrogen is used to replace molecular hydrogen. Different from the traditional hydrogenation, the first step of transfer hydrogenation is the chemisorption of active hydrogen on a catalyst, which was proposed to occur via two reaction mechanisms: 8 (1) the dihydrido metal species formed by the loss of carbon dioxide from metal formato hydrido complex leading to hydrogen transfer from FA to the metal surface (Figure 3a); (2) metal diformate as a key intermediate, which could decompose to generate the dihydrido metal species (Figure 3b).…”
Section: Reaction Mechanisms Of Cth With Famentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of hydrogen donors have been used, including inorganic salts (borohydrides [22][23][24], phosphinates [25]) organic salts (formic acid and its salts [26][27][28], hydrazine·HCl [29,30]), alcohols (butan-2-ol [31], propan-2-ol [32,33]), or proaromatic compounds. Alternatively, CO [34,35] (water-gas shift reaction), zero-valent metal [36][37][38][39] and bimetallic mixtures [40,41] can mediate H 2 O hydrolytic reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Horiuti and Polanyi have introduced a mechanism for CH of alkenes in the presence of heterogeneous catalysts. Moreover, several mechanisms have been reported for CTH in alkenes. , These mechanisms are common to all types of alkenes.…”
Section: Introductionmentioning
confidence: 99%